2017
DOI: 10.1155/2017/5402896
|View full text |Cite
|
Sign up to set email alerts
|

A Multilayer Model Predictive Control Methodology Applied to a Biomass Supply Chain Operational Level

Abstract: Forest biomass has gained increasing interest in the recent years as a renewable source of energy in the context of climate changes and continuous rising of fossil fuels prices. However, due to its characteristics such as seasonality, low density, and high cost, the biomass supply chain needs further optimization to become more competitive in the current energetic market. In this sense and taking into consideration the fact that the transportation is the process that accounts for the higher parcel in the bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Using the kinematic models associated with a differential drive WMR (1) and a reference robot (3), it was found that Complexity 7 velocity profiles and , ensuring ( , , ) → ( * , * , * ), are given by (8) and (9), respectively. On the other hand, profiles of voltages and that applied to DC motors ensure ( , ) → ( , ) are given, according to (19) and (21), as…”
Section: Hierarchical Tracking Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the kinematic models associated with a differential drive WMR (1) and a reference robot (3), it was found that Complexity 7 velocity profiles and , ensuring ( , , ) → ( * , * , * ), are given by (8) and (9), respectively. On the other hand, profiles of voltages and that applied to DC motors ensure ( , ) → ( , ) are given, according to (19) and (21), as…”
Section: Hierarchical Tracking Controlmentioning
confidence: 99%
“…Moreover, not only dynamics of the power stage but also, if required, dynamics associated with the electric power generation should be considered. This is, by itself, an important current research topic [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Soares et al [50] investigated the synchronization of trucks' movement and operation in a full truck pick and delivery problem. Pinho et al [51] propounded a predictive control model to plan vehicle routing. Fokkema et al [52] proposed a continuous-time inventory routing model for a biogas logistic network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inventory management systems represent another important research field, where stochastic reliability measurement and design optimization are the main research directions [22]. Different types of biomass, like energy grass or forest biomass, have gained increasing interest in the recent years as a renewable source of energy, where predictive control methodology approaches in multilayer models become more and more important [23]. Not only design but also control strategies can be represented as NP-hard optimization problems, where simulation methods can also be used to find optimal solutions [24].…”
Section: Literature Reviewmentioning
confidence: 99%